Magnetic higher-mass stars in the early stages of their evolution. Issue Volume 9:Issue S302(2013) (7th August 2014) - Grunhut, Jason H.; Alecian, E.
Abstract: Over the past decade, significant investigations have been made through the use of high-resolution spectropolarimetry to probe the surface magnetic field characteristics of young higher-mass ( M ≳ 1.5 M⊙ ) stars from pre-main sequence to zero-age main sequence evolutionary phases. The results of these observational campaigns suggest that these young higher-mass stars host similar magnetic properties to their main sequence descendants - strong, stable, globally-ordered fields that are detected in approximately 10 percent of all stars. This strongly contrasts with lower-mass stars, where it is generally accepted that a solar-like dynamo is in operation that generates more complex, globally-weak fields that are ubiquitous. The consensus is magnetic fields in higher-mass stars are fossil remnants of a magnetic field present in the molecular cloud, or generated very early during stellar formation. This review discusses the spectropolarimetric observations of higher-mass stars and how these observations have guided our current understanding of the magnetic characteristics of young higher-mass stars.